Quantitative but Not Qualitative Performance Changes in Predictive Motor Timing as a Result of Overtraining - Marková, Lenka; Bareš, Martin; Lungu, Ovidiu V; Filip, Pavel (Cerebellum (London, England), 2020)
The possibilities of substantial long-term improvement of predictive timing might be sometimes seen as limited, with scanty information of neural substrates underlying the potential learning process. To address this issue, we have investigated the performance of 21 baseball professionals and 21 matched controls in a predictive motor timing task previously shown to engage the cerebellum. Baseball players, hypothesized as a model of overtraining of the prediction of future state of the surroundings, showed significantly higher quantitative performance than nonathletic controls, with a substantial part of the baseball players reaching levels far beyond the range observed in common population. Furthermore, the qualitative performance profile of baseball players under various conditions as target speed and acceleration modes did not differ from the profile of healthy controls. Our results suggest that regular exigent training has the potential to vastly improve predictive motor timing. Moreover, the quantitative but not qualitative difference in the performance profile allows us to hypothesize that the selective honing of the same cerebellar processes and networks as in non-trained individuals is the substrate for the quantitative performance improvement, without substantial engagement of further neural nodes.
Keywords: učení; Male; Psychomotor Performance; Baseball; Brain; psychomotorický výkon; Athletes; sportovci; Adult; dospělí; mužské pohlaví; Exercise; Cerebellum; baseball; Predictive motor timing; Learning; lidé; Humans; mozek; Overtraining; Cerebellar learning; cvičení; Time Perception; vnímání času